Statistical Yearbook 2018, Sixty-first Issue - United Nations Department of Economic; Social Affairs (United Nations, 2018)
The Statistical Yearbook is an annual compilation of a wide range of international economic, social and environmental statistics on over 200 countries and areas, compiled from sources including UN agencies and other international, national and specialized organizations. The 2018 edition contains data available to the Statistics Division as of 31 July 2018 and presents them in 33 tables on topics such as: communication; crime; development assistance; education; energy; environment; finance; gender; international merchandise trade; international tourism; labour force; national accounts; population and migration; price and production indices; and science and technology. Most tables covering the period up to 2018. Accompanying the tables are technical notes providing brief descriptions of major statistical concepts, definitions and classifications.